Telecommunication Economics: Selected Results of the COST Action IS0605 - Burkhard Stiller; Antonis M. Hadjiantonis (Springer, 2012)
This book constitutes a collaborative and selected documentation of the scientific outcome of the European COST Action IS0605 Econ@Tel "A Telecommunications Economics COST Network" which run from October 2007 to October 2011. Involving experts from around 20 European countries, the goal of Econ@Tel was to develop a strategic research and training network among key people and organizations in order to enhance Europe's competence in the field of telecommunications economics. Reflecting the organization of the COST Action IS0605 Econ@Tel in working groups the following four major research areas are addressed: - evolution and regulation of communication ecosystems; - social and policy implications of communication technologies; - economics and governance of future networks; - future networks management architectures and mechanisms.
Keywords: 000; Computer Communication Networks; Communications Engineering; Networks; Computers and Society; Management of Computing and Information Systems